An Overview of Competency Development Through Formal Education and Professional Certification Program to Increase the Capacity of BPK - Agus Joko Pramono; Margaretha Keliat (Badan Pemeriksa Keuangan Republik Indonesia, 2022)
The Audit Board of the Republic of Indonesia plays an essential role in ensuring accountability and responsibility for state finance audits. Therefore, auditors must always maintain their competence through continuous professional development. This study describes the competency development program focusing on formal degree education and professional certification for BPK employees. Furthermore, this study measures the adequateness of such a program compared to the allocation in competency development planning, as well as advantages and challenges according to employee perceptions. This study uses secondary data from the 2016-2020 Competency Development Activity Report, the 2019 BPK Peer Review Report, and a questionnaire study. The result shows that BPK has actualized competency development through formal degree education and professional certification program. However, the actualization of competency development with professional certification in 2016-2020 has not yet fully met the allocation stipulated in BPK's Human Capital Development Plan. Employees' perception shows high interest in competency development through formal degree education programs and professional certifications. However, these interests are met with several challenges. One of the challenges that arise involves career advancement and inclusiveness of competency development for all employees, including non-auditor and non-accounting employees. This study suggested further research on conducting a more comprehensive evaluation to ensure that implementing competency development contributes to BPK's capacity.